2020
DOI: 10.1007/s42452-020-03527-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climatic indices (AMO, PDO, and ENSO) and temperature on rainfall in the Northeast Region of India

Abstract: This study explores the spatiotemporal rainfall variability in the Northeast region of India combined with an analysis of the effects of temperature and natural climatic indices [El-Nino Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), and Atlantic Multi-decadal Oscillation (AMO)] on rainfall. The multi-timescale features of rainfall time series for periods 1871-2016 were analysed based on the continuous wavelet transform method. Cross-wavelet and wavelet coherence explore cross-correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…However, Figure 4 shows a low AMO signal in terms of temperature behavior. This is detected in other regions [74]; there are studies [75,76] which report that during the AMO warm phase, the occurrence of droughts is associated with higher temperatures.…”
Section: Temperaturesmentioning
confidence: 71%
“…However, Figure 4 shows a low AMO signal in terms of temperature behavior. This is detected in other regions [74]; there are studies [75,76] which report that during the AMO warm phase, the occurrence of droughts is associated with higher temperatures.…”
Section: Temperaturesmentioning
confidence: 71%
“…Keeping this caveat in mind, we cautiously interpret the multi-proxy record as an increase in seasonality with stronger ISM seasons and longer or drier winters between 3.97 and 3.4 ka BP, followed by decreased seasonality as the ISM weakens and winter moisture picks up again from 3.4 to 3.1 ka BP. Since Dharamjali Cave sits in a transition zone influenced by winter westerlies and the ISM, it is likely that multidecadal shifts in Northern Hemisphere insolation, the Atlantic Meridional Oscillation (AMO) and North Atlantic Oscillation (NAO), as well as the Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO) would play a role in modulating the strength of the dry and wet season rainfall systems and total annual rainfall over Dharamjali Cave, as it does in northeast India 63 . Along with negative NAO conditions, atmospheric blocking patterns over Europe can translate to drier westerlies in the Mediterranean and western Asia, which is one mechanism proposed for the 4.2 ka event 1,64,65 .…”
Section: Resultsmentioning
confidence: 99%
“…This decreasing rainfall is the primary cause of changing the entire hydrological cycle in the region (Dash et al ., 2007; Choudhury et al ., 2019), thereby impacting the regional climate indices. Some studies state that these variabilities might be linked to the impact of El Niño/Southern Oscillation (ENSO), Indian Ocean Dipole (IOD) and Pacific Decadal Oscillation (PDO) through the Indian summer monsoon over the basin (Immerzeel, 2008; Khandu et al ., 2017; Choudhury et al ., 2019; Singh et al ., 2020). It is also found that there is a decreasing trend of rainfall in the monsoon season, with an increasing trend during the pre‐ and post‐monsoon periods over India (Dash et al ., 2007; Deka et al ., 2013; Das et al ., 2015; Mukherjee et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%